Natural killer cells and innate lymphoid cells but not NKT cells are mature in their cytokine production at birth - Swieboda,D; Thwaites,R; Rice,T; Guo,Y; Nadel,S; Openshaw,P; Holder,E; Culley,F (Clinical and Experimental Immunology, 2024)
Early life is a time of increased susceptibility to infectious diseases and development of allergy. Innate lymphocytes are crucial components of the initiation and regulation of immune responses at mucosal surfaces, but functional differences in innate lymphocytes early in life are not fully described. We aimed to characterise the abundance and function of different innate lymphocyte cell populations in cord blood in comparison to that of adults. Blood was collected from adult donors and umbilical vessels at birth. Multicolour flow cytometry panels were used to identify and characterise lymphocyte populations and their capacity to produce hallmark cytokines. Lymphocytes were more abundant in cord blood compared to adults, however, mucosal-associated invariant T (MAIT) cells and Natural Killer T (NKT)-like cells, were far less abundant. The capacity of NKT-like cells to produce cytokines and their expression of the cytotoxic granule protein granzyme B and the marker of terminal differentiation CD57 were much lower in cord blood than in adults. In contrast, Natural Killer (NK) cells were as abundant in cord blood as in adults, they could produce IFNγ, and their expression of granzyme B was not significantly different to that of adult NK cells, although CD57 expression was lower. All innate lymphoid cell (ILC) subsets were more abundant in cord blood, and ILC1 and ILC2 were capable of production of IFNγ and IL-13, respectively. In conclusion, different innate lymphoid cells differ in both abundance and function in peripheral blood at birth and with important implications for immunity in early life.